Weed control and green ear yield in maize - Silva,P.S.L. (2004)
The objective of this work was to evaluate the influence of weeding frequency on cultivar Centralmex green corn yield. Two experiments were conducted in Mossoró-RN (Brazil), with the use of sprinkler irrigation. A random block design with four replicates was used. It was observed that the total number and weight (TW) of unhusked green ears, the number and weight of marketable unhusked ears and the number and weight of marketable husked ears were reduced under no weeding treatment. The number timing of weedings did not influence green corn yield, except for one weeding at 60 DAP, which was equivalent to the "no weeding" treatment, for TW. When maize is marketed considering the total number of green ears, higher net income is obtained when one weeding is carried out 45 days after planting.